2004
DOI: 10.1023/b:psaq.0000031797.74295.f8
|View full text |Cite
|
Sign up to set email alerts
|

A Culture of Enquiry: Research Evidence and the Therapeutic Community

Abstract: This paper presents data from a systematic review and meta-analysis of 29 published studies of therapeutic community effectiveness using controls, including 8 randomised control trials. Metaregressions suggest that the two types of therapeutic community, democratic and concept-based, and the age of the study, are the key sources of heterogeneity in the collection of studies analysed.Otherwise, heterogeneity is low and the meta-analysis confirms the effectiveness of therapeutic community treatment with overall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 21 publications
3
79
1
6
Order By: Relevance
“…From these results, studies having the following characteristics were selected: (i) comprised of a matched-control trial or RCT and (ii) compared TC with a different type of treatment (rather than no treatment or early discharge from the TC). These criteria are more stringent than the ones used by Lees et al (2004) who permitted matchedcontrol trials comparing dropouts and completers from the same TC; thus, we do report below on some such studies that were identified by Lees et al (2004). We did, however, include studies where the control condition was standard incarceration, or treatment that was less frequent than the TC programme; yet such studies also have clear methodological limitations since it is possible that a non-TC treatment of similar frequency could produce equal or better outcomes.…”
Section: Effectiveness Of Therapeutic Communities: a Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, studies having the following characteristics were selected: (i) comprised of a matched-control trial or RCT and (ii) compared TC with a different type of treatment (rather than no treatment or early discharge from the TC). These criteria are more stringent than the ones used by Lees et al (2004) who permitted matchedcontrol trials comparing dropouts and completers from the same TC; thus, we do report below on some such studies that were identified by Lees et al (2004). We did, however, include studies where the control condition was standard incarceration, or treatment that was less frequent than the TC programme; yet such studies also have clear methodological limitations since it is possible that a non-TC treatment of similar frequency could produce equal or better outcomes.…”
Section: Effectiveness Of Therapeutic Communities: a Systematic Reviewmentioning
confidence: 99%
“…The vast majority of the identified studies relate to substance misuse and/or forensic services, including six of the eight RCTs identified by Lees et al (2004). There is some (limited) evidence for secure TCs being superior to standard prison services (in terms of reducing risk of future offending behaviour) and very little evidence for TCs being superior to standard treatment for substance abuse.…”
Section: Effectiveness Of Therapeutic Communities: a Systematic Reviewmentioning
confidence: 99%
“…Although DTCs are not included within the National Institute for Clinical Excellence (NICE) guidelines for the treatment of PD (Antisocial PD -NICE, 2010; Borderline PD -NICE, 2009), they continue to be used in community and forensic settings with promising results (Lees et al, 2004;Warren et al, 2003). The limited 'gold standard' evidence base (otherwise known as Randomised Controlled Trials -an experimental design involving random allocation to treatment and control conditions) for this intervention compared to other developing psychotherapy treatments for this client population, such as Cognitive Behaviour Therapy (CBT) and Dialectical Behaviour Therapy (DBT) (NICE, 2009) has prevented its inclusion within treatment recommendations (Pearce & Autrique, 2010).…”
Section: A Summarised History Of Treatment Evaluation and Some Methodmentioning
confidence: 99%
“…This inclusion criterion was used in a previous review (Lees et al, 2004). Studies that focused on different models of TC (e.g.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation